Comparison of time-motion, heart rate responses, and training load measurement in Brazilian jiu-jitsu heavyweight and lightweight fighters: a cross-sectional study - Bassettia, V. L.; da Costaa, J. V. M.; Tasinafo Júnior, M. F.; Bertochi, G. F. A.; Foresti, Y. F.; Gomesa, A. Z.; Puggina, E. F. (International Journal of Performance Analysis in Sport, 2024)
This study compares technical-tactical and physiological parameters between lightweight and heavyweight male Brazilian Jiu-Jitsu (BJJ) fighters. We included 11 adult BJJ fighters (lightweight: age = 28 ± 7 years; body mass = 73 ± 2 kg; height = 1.72 ± 0.7 m; body mass index = 25 ± 2 kg/m2; heavyweight: age = 27 ± 3 years; body mass = 95 ± 6 kg; height = 1.87 ± 0.6 m; body mass index = 27 ± 2 kg/m2). Six participants were considered lightweight (71 to 77 kg) and five heavyweight divisions (88 to 101 kg). Initially, sample characteristics and a graded exercise test determined the physiological parameters. A simulated competition (10 minutes maximum) assessed technical-tactical characteristics, Heart Rate (HR), Rate of Perceived Exertion (RPE), TRaining IMPulse based on HR, session-RPE, and time at HR intensity zones (Z1, Z2, and Z3). A comparison test revealed that heavyweight athletes exhibited a higher height, body mass, total time in low-intensity efforts per block, number of standing combat blocks, and less time in high-intensity efforts per block and lower VO2MAX than lightweight (p < 0.05). The HR showed a nonlinear increase throughout each minute of the fights, with the heavyweight division demonstrating predominantly higher HR values. All fighters accumulated more time in training zone 3. The physiological and temporal differences between divisions suggest that BJJ training must be designed specifically for lightweight or heavyweight divisions.